PEREMPUAN PEMBUAT BATU MERAH DI DESA GUALI KECAMATAN KUSAMBI KABUPATEN MUNA BARAT - Wa ODe Kota; Ashmarita . . (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2015)
This study aims to determine and describe the women in the village of red stone maker Guali, District kusambi. In this study, using the theory fenism by Naomi Wolf. As a method of study based on field research, the technique of data collection is done through observation (observation) and interview (interview). Data were analyzed by descriptive qualitative. The results showed that the activities of women workers in red stone industry in the Village Guali starts from making dough, prints, dries, to the stage of transporting bricks from place to place wards drying or burning. The women work as a maker of bricks has some fundamental reasons, among others: the limited employment opportunities, urgency of economic, agricultural land is no longer productive, and to help the family economy, especially for the cost of daily living and for children's education. Wage system in this venture is determined by the business owners. Wages were taken in three parts, namely the process of making dough and molding, drying and transporting process of kiln to kiln. Wage received depends on the number of red rock that managed by women workers mereah stone itself. Keywords: women, and the maker of bricks